A bifunctional solid oxide electrolysis cell for simultaneous CO2 utilization and synthesis gas production. Issue 94 (7th November 2016) - Sun, Yi-Fei; Wu, Yi-Yang; Zhang, Ya-Qian; Li, Jian-Hui; Luo, Yu; Shi, Yi-Xiang; Hua, Bin; Luo, Jing-Li
Abstract : Herein, we report a pioneering solid oxide cell which consumes CO2 to produce CO at the cathode side and simultaneously synthesizes valuable syngas at the anode side via a one-step green process. Abstract : We hereby report on a pioneering and inspiring solid oxide cell which, assisted by natural gas, utilizes a bifunctional electrolysis cell configuration to effectively consume CO2 to produce CO at the cathode side and simultaneously synthesize highly valuable syngas (mixture of CO and H2 ) at the anode side via a one-step green process.